Spatial pattern analysis of land cover changes using Fragstat in Kendal Delta, Kendal Regency, Central Java - Fitri Hastari Nur Rizki (EDP Sciences, 2021)
The northern coastal plains of Kendal Regency are deltaic landform whose processes are strongly influenced by fluvial (fluvial dominated deltas). The area of land in the Kendal Delta area continues to experience changes due to regional developments that occur as Kendal Regency is designated as one of the national activity center in terms of strategic and industrial economies. Various developments can trigger various land conversions so that studies are needed to identify changes occurring. The purpose of this study is to identify land cover patterns based on geomorphological aspects and analyzed land cover changes based on landscape structures in Delta Kendal in 1989 and 2021. Changes in the Kendal Delta landscape structure were analyzed using landscape metrics approach. The results showed that the land cover pattern in the Kendal Delta from 1989 to 2021 has a change. Based on the calculation from landscape metrics, land cover in Delta Kendal that has a relatively high patch density tends to have a high level of interference, and vice versa. In general, there is a relationship if there is an increase in the value of PD and ED, there will be a decrease in the value of MNN and IJI.